2011
DOI: 10.4102/ojvr.v78i1.305
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the livestock ticks of the North West province, South Africa

Abstract: Ticks, as vectors of disease and damage agents, impact directly and indirectly on the economy of the livestock industry in southern Africa. This study surveyed the occurrence and distribution of ticks infesting livestock across the North West province, South Africa. During three phases in consecutive years, officers of the provincial Veterinary Department collected specimens monthly from livestock hosts at specified sites across the province. Data analysis constituted the fourth phase of the study. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 15 publications
8
45
1
Order By: Relevance
“…Its distribution was fairly constant in all the ecological regions of Zimbabwe. It has been reported that R. evertsi evertsi tolerates a wide range of climatic conditions (Walker et al, 2000) and is widely distributed and common on livestock throughout much of Africa (Spickett et al, 2011). Similar results on the widespread distribution of R. evertsi evertsi in Zimbabwe were also reported by Hove et al (2008) and Ndhlovu et al (2009).…”
Section: Farmers and Veterinary Extensionsupporting
confidence: 76%
See 2 more Smart Citations
“…Its distribution was fairly constant in all the ecological regions of Zimbabwe. It has been reported that R. evertsi evertsi tolerates a wide range of climatic conditions (Walker et al, 2000) and is widely distributed and common on livestock throughout much of Africa (Spickett et al, 2011). Similar results on the widespread distribution of R. evertsi evertsi in Zimbabwe were also reported by Hove et al (2008) and Ndhlovu et al (2009).…”
Section: Farmers and Veterinary Extensionsupporting
confidence: 76%
“…Hyalomma species are very common particularly in the drier parts of southern Africa (Walker, 1991), in this study the prevalence of H. rufipes was significantly higher than that of H. truncatum (confidence intervals of their prevalence do not overlap). Previous studies have shown that H. truncatum has a widespread distribution in Zimbabwe as compared to H. rufipes (Norval, 1982, Hove et al, 2008; this could not be observed in this study mainly because of the tendency of this tick to attach to the tail switch which is mostly overlooked during sampling, such observations were also made by Spickett et al (2011). It is also noteworthy, however, that H. rufipes was found in the central and north central part of the country which indicated movement of this tick especially when looking at past published records.…”
Section: Farmers and Veterinary Extensioncontrasting
confidence: 57%
See 1 more Smart Citation
“…According to the farmer, these animals had been bought in North-West Province, South Africa, in 2005. In a survey on the distribution of ticks in this province, conducted over a number of years, commencing in 2001, Spickett et al (2011) recorded R. microplus at 14 localities, thus supporting the possibility of its introduction into Namibia from here.…”
Section: Discussionmentioning
confidence: 66%
“…On the African continent R. microplus is common along the eastern coastal belt and also in the summer rainfall northern regions of South Africa (Howell et al 1978;T¢nnesen et al 2004;Horak et al 2009;Spickett et al 2011). It is also present in Swaziland, Mozambique, Zimbabwe and Zambia (Mason and Norval 1980;Berkvens et al 1998;Wedderburn et al 1999;Horak et al 2009).…”
Section: Introductionmentioning
confidence: 99%